Behavioral aspects in implementing integrated management systems – ERP - Côrtes, Pedro Luiz; Lemos, Mauro Tadeu Silveira (Revista Gestão da Produção Operações e Sistemas, 2009)
The use of ERP systems (Enterprise Resource Planning) by organizations has increased due to the perspective of improvement in processes, adoption of more efficient controls and elimination of duplicated efforts. Never- theless, organizations still face problems in implementing these systems. This study is the result of a survey about behavioral issues related to the use of ERPs. The population consisted of people who participated in ERP implementation like service providers, administrators, company executives and users. The sample consisted of 162 people who expressed their degree of agreement using a Likert scale. The responses received were processed using SPSS (Statistical Package for Social Sciences). Descriptive statistics parameters and graphs were obtained, facilitating analysis and interpretation. It wasthus possible to provide subsidies to other research that deepen the scope of this study, expanding the conclusions drawn. Keywords: ERP; Enterprise Resource Planning; Systems Implementation.